Effect of heat loss on turbulent buoyancy-driven flow in a rectangular cavity using the large-eddy simulation. (1st October 2016) - Tkachenko, Svetlana A.; Lau, Ghar E.; Timchenko, Victoria; Yeoh, Guan H.; Reizes, John
ABSTRACT: Large-eddy simulations (LESs) investigating the effect of heat loss on buoyancy-driven flow in a tall rectangular cavity are performed. A time-dependent one-dimensional energy balance approach is utilized to model the heat loss at the top wall. Compared with the experimental data and numerical results for a perfectly adiabatic case, allowing heat loss at the top wall alters both the time-averaged and instantaneous flow and the thermal fields and constitutes a delay in the relaminarization process. Intense recirculation flows exist adjacent to both the top and bottom walls, thereby triggering the earlier formation of vortex cores along both the hot and cold walls.